Efficient mesophyll-derived protoplast manipulation system as a versatile tool for characterization of genes responding to multiple stimuli in mulberry - Zhou, H.; Lei, Y.; Hou, Z.; Yuan, J.; He, N.
Mulberry serves as a crucial element of the global sericulture industry. Functional gene analysis considering resistant traits improvement of mulberry is greatly hindered by its long life cycle and recalcitrance to genetic transformation. A versatile protoplast manipulation system enables rapid and effective transformation for gene functional studies, especially on physiological perceptions and responses to hormones, metabolites, and environmental stimuli is urgently demanded. In this study, we optimized the protocol for isolating mesophyll-derived protoplast from sterile cultures of Morus alba cv. GY62. With sufficient viable protoplasts, polyethylene glycol (PEG)-mediated transient gene expression was developed and a transformation efficiency of nearly 50 percent was achieved through optimizing the incubation strategy. The transient gene expression system was validated by subcellular localization assays of the mulberry nuclear marker gene MaHTR6 and chloroplast marker gene MaTRX. Furthermore, the system was used for functional characterization of putative mulberry cytokinin response factors (MaCRFs)in response to phytohormone and environmental stimuli. Combined the established system with RT-qPCR to test the MaCRFs transcriptional regulation, we found that among the three MaCRFs, conserved with Arabidopsis CRF2, MaCRF1 turned out to function primarily as a response factor to cytokinin and auxin. While MaCRF2 and MaCRF3 respond not only to phytohormones but also to environmental stresses. In summary, we have established an efficient mesophyll-derived protoplast manipulation system in mulberry, thereby facilitating transient functional screening of CRF genes in response to multiple external stimuli.
Keywords: PROTOPLAST; MULBERRY; CYTOKININ RESPONSE FACTOR; STRESS RESPONSE; TRANSIENT GENE EXPRESSION; SUBCELLULAR LOCATION